Unmittigated Communion, Psychological Entitlement and Intimate Relationships - Kamenov, Željka (2011)
What role do unmittigated communion (excessive focus on others and their needs) and psychological entitlement (a sense of being more deserving than others) play in relationship behavior? We hypothesized that individuals with higher unmittigated communion will show love in more specific ways, and be more affectionate and less negative in their marriage, while the reverse was expected for psychological entitlement. We gahered data from 302 Croatian married couples of varied ages. Spouses filled out standard scales measuring unmittigated communion, psychological entitlement, and reported on the ways their partner shows love, as well as how affectionte and negatively their partner behaves toward them. Men and women with higher unmittigated communion show more love (both instrumentally and expressively) and are more affectionate (women only). Unmitigated commuion was not associated with negative behavior. Entitled individuals behave more negatively, but we found no differences for other types of behavior.